Diffusion of the use of biodegradable coating to family farmers in the State of Goiás, Brazil (Research, Society and Development, 2020)
The act of evaluating the diffusion of an innovation is extremely important and certainly surpasses the advent of innovation. Therefore, the objective of work was to evaluate the spread of the use of biodegradable coating to family farmers in the State of Goiás, Brazil. Qualitative research was carried out through questionnaires in 20 rural properties in the municipality of Jaraguá - GO, in two stages: stage 1 in January 2019; stage 2 in July 2019. The data were submitted to multivariate analysis, by means of cluster analysis, organized in a dendrogram type graph, using the Jaccard distance matrix and the complete link cluster technique (most distant neighbor). Under the conditions in which the work was carried out, there was low acceptance and diffusion of the use of biodegradable coating by family farmers, due to the fact that they have a low level of education, do not use technology, as well as irrigation or machinery, in addition their properties are distant (>10km) from urban centers.